Ultrafast laser frequency tuning based on equivalent optical phase sampling and accumulation - Weiqiang Lyu; Huan Tian; Zhenwei Fu; Lingjie Zhang; Zhen Zeng; Yaowen Zhang; Heping Li; Zhiyao Zhang; Yong Liu (APL Photonics)
Ultrafast laser frequency tuning is a crucial function in numerous applications, including light detection and ranging (LiDAR), optical coherence tomography (OCT), and spectroscopy. In general, laser frequency tuning is realized via the motion of mechanical structures, frequency-swept optical filters, or the Pockels effect in the laser cavity. Nevertheless, the maximum frequency tuning rate and sweep rate are smaller than 107 THz/s and 1 GHz, respectively, due to the inherent speed limitation of the existing tuning mechanisms. Here, we propose and demonstrate a brand-new concept for ultrafast laser frequency tuning, which is realized based on equivalent optical phase sampling and accumulation in the laser cavity. By inserting an electro-optic phase modulator (PM) into the laser cavity and properly setting the period of the driving signal applied to the PM to make its integer multiple slightly deviate from the round trip time of the laser cavity, a linear mapping from the voltage of the driving signal to the output laser frequency is realized via equivalent optical phase sampling and accumulation. This remarkable feature provides a rapid way to manipulate the laser frequency, breaking the frequency tuning speed limitation of the existing approaches. In the experiment, a record-breaking frequency tuning rate of 1.522 × 109 THz/s and a sweep rate of 2223.97 MHz are simultaneously realized. Moreover, the center wavelength and the frequency tuning range can be easily reconfigured. This work paves the way for ultrafast laser frequency tuning in a customized wavelength range.